Production of new multi-coupling reactions of PS and PCSOC bonding by bimetallic of magnetic nanocatalyst - Mansour Binandeh (Nano Trends)
In this study, a new magnetic nanocatalyst with a heterogeneous structure was used, and its application in new multiple coupling reactions was investigated. The structure of this new nanocatalyst Fe3O4@SiO2/C (CPTES)L (ligand)/Co/Cu was confirmed by VSM, SEM, EDX, and other analyses. The new coupling reaction involved the formation of multiple bonds, including sulfur bonding with two phosphorus and oxygen atoms, which was carried out in a domino manner. The formation of phosphorus-sulfur and carbon-oxygen-carbon-phosphorus bonds was accompanied by an efficiency of more than 95%, and the optimal catalytic dosage was about 0.02 mol%. This nanocatalyst has the ability to be used repeatedly during the reaction and was evaluated using the molar percentage to molecular weight analysis of the nanocatalyst after several washings, drying, and weighing. The results showed that after 10 cycles of recovery from the nanocatalyst in repeating the coupling reactions, its recovery power was reported to be about 94%. What was unique was the performance of multiple coupling reactions, which included the creation of new products proposed to be used as prodrugs in the medical industry due to their structural similarity with hypnotic and Alzheimer's drugs. Research in the medical field could provide a bright horizon for the development of targeted drug delivery systems.